Aksara Bali dalam Konteks Multikulturalisme: Menjaga Warisan Lokal di Tengah Globalisasi - Brahmandika, Pande Gede; Sugiarka, I Gede (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Balinese script is one of the cultural heritages that plays an important role in maintaining the cultural identity of the Balinese people. In the midst of increasingly strong globalization, the existence of Balinese script faces various challenges, including the influence of foreign cultures and changes in local values. This article aims to explore how Balinese script can be maintained and developed in the context of increasingly complex multiculturalism. Through a qualitative approach, this study analyzes various efforts to preserve Balinese script involving education, communities, and the role of modern technology. The results of the analysis show that the integration of Balinese script in the education system, the use of digital technology, and support from local communities and the government are key to maintaining the sustainability of this cultural heritage. This article also highlights the importance of collective awareness in preserving Balinese script as a symbol of unique and valuable cultural identity amidst global cultural diversity